2013
DOI: 10.1111/2041-210x.12023
|View full text |Cite
|
Sign up to set email alerts
|

Undersampling and the measurement of beta diversity

Abstract: Summary1. Beta diversity is a conceptual link between diversity at local and regional scales. Various additional methodologies of quantifying this and related phenomena have been applied. Among them, measures of pairwise (dis)similarity of sites are particularly popular. Undersampling, i.e. not recording all taxa present at a site, is a common situation in ecological data. Bias in many metrics related to beta diversity must be expected, but only few studies have explicitly investigated the properties of variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
147
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(159 citation statements)
references
References 49 publications
8
147
1
Order By: Relevance
“…Although this reduces bias compared with uncorrected species counts, mathematical methods for incorporating additional features of the study design, such as site-or survey-specific covariates affecting species' detection ( Figure 1), are not straightforward or often not possible [36]. Beta-diversity indices of community similarity are frequently calculated without correcting for imperfect detection [73] and their performance in the face of undetected species is variable [45,74]. The ChaoJaccard/Sorensen index [45,73] is one of the few betadiversity estimators that corrects for sampling bias by estimating the contribution of undetected species using the probability that individuals drawn randomly from the sample belong to a species shared by the two assemblages, based on species' relative abundances or occurrences.…”
Section: Comparison Of Detection-based Estimators Of Diversity With Tmentioning
confidence: 99%
“…Although this reduces bias compared with uncorrected species counts, mathematical methods for incorporating additional features of the study design, such as site-or survey-specific covariates affecting species' detection ( Figure 1), are not straightforward or often not possible [36]. Beta-diversity indices of community similarity are frequently calculated without correcting for imperfect detection [73] and their performance in the face of undetected species is variable [45,74]. The ChaoJaccard/Sorensen index [45,73] is one of the few betadiversity estimators that corrects for sampling bias by estimating the contribution of undetected species using the probability that individuals drawn randomly from the sample belong to a species shared by the two assemblages, based on species' relative abundances or occurrences.…”
Section: Comparison Of Detection-based Estimators Of Diversity With Tmentioning
confidence: 99%
“…The confounding of imperfect detection with ecological parameters has been observed in the single species situations for population extinction and colonization rates (Moilanen 2002;Ke´ry 2004;Ke´ry et al 2006;. Beck et al (2013) also showed that most metrics measuring community differences are susceptible to incomplete sampling, and called for the development of robust metrics. In our simulation experiments, although we assumed that detection probability of individual species was constant among the sampling sites, this assumption cannot be always accepted in field surveys.…”
Section: Location Of An Indicator Variable In the Hierarchical Model mentioning
confidence: 99%
“…ANOSIM, NMDS, hierarchical clustering, and PERMANOVA were conducted using all non-singleton OTU (i.e., those occurring more than once in the entire dataset) to minimize the potential under-estimation of similarity due to undersampling (Manter & Bakker, 2015). The Morisita-Horn metric of similarity was used to minimize sensitivity to under-sampling, as it reflects the distribution of abundant taxa (Beck, Holloway & Schwanghart, 2013). Host individuals/leaf types from which <4 isolates were sequenced were excluded from all analyses (see Table 1).…”
Section: Methodsmentioning
confidence: 99%